2012
DOI: 10.1007/s10815-012-9875-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection criteria for blastocyst transfers in extended embryo culture programs

Abstract: Purpose To identify the correlation between different cycles, patient factors and blastocyst characteristics. Methods The study included 420 patients undergoing ICSI cycles and 2781 graded blastocysts, which took into account the blastocyst quality. The correlations between the blastocyst parameters and the patient and cycle characteristics were assessed. Results The blastocyst development was negatively correlated with the maternal age, BMI and dose of FSH. The ICM was negatively correlated with the FSH dose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Single blastocyst transfers have the additional advantages of increasing pregnancy rates and reducing multiple gestations because of their high implantation rates [10,11]. While blastocyst transfer is beneficial in good prognosis patients, the same is not true for unselected groups of patients [12]. Therefore, some assisted reproduction centers may avoid adopting extended embryo cultures due to an unpredictable rate of blastocyst development.…”
Section: Introductionmentioning
confidence: 99%
“…Single blastocyst transfers have the additional advantages of increasing pregnancy rates and reducing multiple gestations because of their high implantation rates [10,11]. While blastocyst transfer is beneficial in good prognosis patients, the same is not true for unselected groups of patients [12]. Therefore, some assisted reproduction centers may avoid adopting extended embryo cultures due to an unpredictable rate of blastocyst development.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the incidence of cancelled transfers may be higher in unselected patients. It has been previously described that poor embryo morphology on days two and three of development do not favour blastocyst formation [32]. There is a general consensus that low quality embryos may have an increased implantation chance when incubated in vivo compared to in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that the transfer of blastocysts drastically increases the implantation rate [28][29][30][31], we have previously reported that extended culture may not favour embryos with poor morphology on days two and three of development [32]. However, it is unclear whether transfer of low quality embryos at the cleavage stage is a better approach than culturing these embryos until day five.…”
Section: Introductionmentioning
confidence: 85%
“…ICSI and embryo culture, quality and transfer ICSI was performed according to Palermo et al (1992). High-quality embryos and blastocysts are defined elsewhere (Braga et al, 2012). Embryo transfer was performed on day 5 using a soft catheter with transabdominal ultrasound guidance.…”
Section: Controlled Ovarian Stimulationmentioning
confidence: 99%